2012
DOI: 10.1021/cm301979y
|View full text |Cite
|
Sign up to set email alerts
|

Blue Emission by Interstitial Site Occupation of Ce3+in AlN

Abstract: An AlN phosphor that was coactivated by Ce 3+ and Si 4+ ions was synthesized by gas pressure sintering (GPS) at 2050 °C for 4 h in a 0.92 MPa nitrogen atmosphere. The phosphor emits blue color with the Commission International de l'Eclairage (CIE) chromaticity coordinate of (0.15, 0.07), which is close to the National Television Standard Committee (NTSC) blue coordinate. The crystallization and cell parameters of the samples were investigated by Rietveld refinement and high-resolution transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…Therefore, its amount is very low and the influence of it on structure and optical properties can be ignored. The high Si-N concentration of Al 10 [17]. Later, it is experimentally observed that Ce is actually incorporated inside [17].…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, its amount is very low and the influence of it on structure and optical properties can be ignored. The high Si-N concentration of Al 10 [17]. Later, it is experimentally observed that Ce is actually incorporated inside [17].…”
Section: Resultsmentioning
confidence: 96%
“…14 McCrate et al also presented that the intrinsic oxygen vacancy defect (OVD) on planar fused silica was experimentally detected by titration with fluorescent probe molecules, such as perylene-3methanamine and 3-vinyl perylene. 18 Blue emission by Ce 3+ ions occupied in the interstitial site of AlN structure was reported by Liu et al 19 According to their results, an octahedral interstitial site of the AlN compound with würtzite structure was proposed to be the site for Ce 3+ ions because the ionic size of Ce 3+ ions is much larger than that of Al 3+ . It should be noted that there is an interstitial sites formed structurally in the crystal lattice of α-quartz (or.…”
Section: Introductionmentioning
confidence: 92%
“…1 Among them, aluminum nitride (AlN) has been studied as a new class of nitride host for the phosphors owing to its wide bandgap (6.2 eV), high thermal conductivity and high stability. 1,2 To date, activators such as rare-earth [3][4][5][6][7][8] and Mn 9,10 doped AlN phosphors have been reported for utilization in LEDs and FEDs. Especially, AlN:Mn is one of the promising phosphor because it can emit bright orangered color owing to the transition of 3d-electrons in a Mn ion.…”
mentioning
confidence: 99%
“…Therefore, the critical distance was calculated to be 11 Å, which is close to the typical value of R c (15 Å), indicating that the incorporation of Mn 2þ ions in the AlN host should be involve substitution of the ions of the host lattice. 8 The CIE chromaticity diagram of AlN:3%Mn 2þ phosphor is shown in Fig. 6.…”
mentioning
confidence: 99%